(untitled) (Fiep Bulletin - online, 2015)
Patients with HIV/Aids undergo conflictive physical and emotional situations in addition to aggressive drug therapy involving significant behavioral changes. The professional becomes the mediator of facilitating attitudes with respect to prevention and treatment. The purpose of this study was identify positive relational attitudes in professional care, from the perception of patients with HIV/AIDS at a major state medical service in Natal, Brazil. It is a qualitative study using semi-structured interviews with 34 patients, and content analysis technique for textual data interpretation. There was a predominance of the 31 to 45 year age group (50%), homogeneity as to sex, without conjugal union (73.53%), low education level (67.65%), unemployed (61.76%).From the analysis of the textual content of the interviews, four categories emerged: 1) Facing the infirmity, 2) Professionals perceived as technicians, 3) Empathetic attitudes, 4) Level of satisfaction. The appearance of AIDS rouses feelings of anger, discrimination and threatening memories. Patients perceive the technical competence of professionals, associated to interaction difficulties and incongruent attitudes. There is a lack of “looking patients in the eye” and of “listening” as a set of expressions necessary to empathetic coherence. In relation to care, a welcoming environment, respect for privacy and humanization of services are the principles of interactive relations. The study reveals significant associations in relation to inadequate organization in the services and professional teams, thus interfering in the quality of care. There is evidence of care with the disease and in its treatment, but with limitations in listening and understanding, preventing an integrated view of patients as active subjects who indicate, demand and share their needs. Fragments of this encounter need to be reformulated to enable facilitating attitudes of a humanized know-how between professional-patient.